Preparation of Nano‐bismuth with Different Particle Sizes and the Size Dependent Electrochemical Thermodynamics. Issue 7 (5th April 2019) - Wang, Mengying; Cui, Zixiang; Xue, Yongqiang; Yan, Aijie; Yu, Xing; Song, Xinru; Li, Hongxing
Abstract: Nano‐bismuth has excellent electrochemical properties. However, it is still unclear how the particle size of nano‐bismuth influences its electrochemical thermodynamic properties. In this paper, spherical bismuth nanoparticles with different particle sizes were prepared by solvothermal method; the electrode potentials, the temperature coefficients of the electrode potentials and the thermodynamic functions of reaction for nano‐bismuth electrodes with different particle sizes at different temperatures were determined; and the effects of particle size on the electrode potential, the temperature coefficient and the thermodynamic functions were discussed. The experimental results show that particle size of bismuth nanoparticles has a significant influences on the electrochemical thermodynamic properties. The standard electrode potential of the nano‐bismuth electrode with a diameter of 39.9 nm was 0.009 V lower than that of the ordinary standard electrode (0.308 V); the temperature coefficient of the electrode potential with a diameter of 39.9 nm was nearly double that of 85.9 nm. With the particle sizes decrease, the standard molar Gibbs energy of reaction, the standard molar enthalpy of reaction, the standard molar entropy of reaction, the molar reversible reaction heat and the temperature coefficient increase; and these quantities are linearly related to the reciprocal of the particle diameter. Abstract :